Animated Video Media on Breakfast Behavior Analysis of Nutritional Education Effect Through - Fitriani Fitriani; Teungku Nih Farisni; Yarmaliza Yarmaliza; Fitrah Reynaldi; Zakiyuddin Zakiyuddin; Safrizal Safrizal; Onetusfifsi Putra; Veni Nella Syahputri (Universitas Aisyah Pringsewu, 2023)
A preliminary study of 10 Alue Buloh students showed that 8 of them did not know the benefits of breakfast and the impact of not having breakfast and overall they had mistaken perceptions about proper nutritional intake for their morning activities. The purpose of this study was to investigate the effect of nutritional education through animated video media on breakfast behavior in elementary school children. The research design used was quasi experiment, with a pre-test and post-test design applying one group with a total sample size of 50 students. The sampling technique was purposive sampling. The criteria were: willing to be the sample, never received counseling about breakfast, and were in good health condition Interventions were carried out at 6 times with a span of 2 months. The data analysis used was univariate analysis and bivariate analysis using the Dependent t test.The results showed that there was an effect of nutritional education using animated video media on knowledge with p value p(sig) = 0.000, there is an effect of nutritional education using animated video media on student attitudes, there is an effect of nutritional education using animated video media on student actions. Therefore, it is suggested that socialization and education is absolutely needed to be applied in other elementary schools through animated video media since it is very interesting and motivates good behavior change on the importance of breakfast. Abstrak: Berdasar sebuah studi pendahuluan terhadap 10 siswa di Alue Buloh menunjukkan bahwa 8 orang diantaranya tidak mengetahui manfaat sarapan dan dampak dari tidak sarapan dan secara keseluruhan mereka memiliki persepsi yang salah tentang asupan nutrisi yang tepat untuk aktivitas pagi mereka. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pendidikan gizi melalui media video animasi terhadap perilaku sarapan pagi pada anak sekolah dasar. Rancangan penelitian yang digunakan adalah eksperimen semu, dengan desain pre-test dan post-test apply one group dengan jumlah sampel sebanyak 50 siswa. Teknik pengambilan sampel adalah purposive sampling. Kriterianya adalah: bersedia menjadi sampel, tidak pernah mendapat penyuluhan tentang sarapan pagi, dan dalam keadaan sehat Intervensi dilakukan sebanyak 6 kali dengan rentang waktu 2 bulan. Analisis data yang digunakan adalah analisis univariat dan analisis bivariat dengan menggunakan uji Dependent t. Hasil penelitian menunjukkan bahwa ada pengaruh pendidikan gizi menggunakan media video animasi terhadap pengetahuan dengan p value p(sig) = 0,000, ada pengaruh pendidikan gizi menggunakan media video animasi terhadap sikap siswa, ada pengaruh pendidikan gizi menggunakan media video animasi media video animasi tentang aksi siswa. Oleh karena itu disarankan sosialisasi dan edukasi mutlak perlu diterapkan di sekolah dasar lainnya melalui media video animasi karena sangat menarik dan memotivasi perubahan perilaku yang baik tentang pentingnya sarapan pagi.